2017
DOI: 10.1111/bjd.15151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high-mobility group box 1 on melanocytic survival and its involvement in the pathogenesis of vitiligo

Abstract: External stimuli (e.g. oxidative stress and ultraviolet irradiation) may trigger HMGB1 release by keratinocytes, thereby perpetuating vitiligo through HMGB1-induced melanocytic apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…This confirmed the role of autocrine HMGB1 in the expression of Nrf2 and its downstream genes. Kim et al have reported that recombinant HMGB1 protein induced by external stimuli led to melanocyte apoptosis. The HMGB1 used in their experiments was exogenous recombinant HMGB1, which does not reflect the role of HMGB1 in melanocytes.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This confirmed the role of autocrine HMGB1 in the expression of Nrf2 and its downstream genes. Kim et al have reported that recombinant HMGB1 protein induced by external stimuli led to melanocyte apoptosis. The HMGB1 used in their experiments was exogenous recombinant HMGB1, which does not reflect the role of HMGB1 in melanocytes.…”
Section: Discussionsupporting
confidence: 85%
“…These data showed that oxidative stress may be a common mechanism for regulating the translocation, release and activity of HMGB1, including in NHEMs. A couple of reports have demonstrated that HMGB1 is expressed in keratinocytes and released from them under ultraviolet radiation or H 2 O 2 treatment. As shown in Figures and , HMGB1 is mainly expressed in the nucleus of NHEMs and is translocated from the nucleus to the cytoplasm after exposure to low doses of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, Kim et al . suggest the potential role of HMGB1 from keratinocytes in melanogenesis and demonstrate that secretion of HMGB1 from neighbouring keratinocytes influences melanocyte survival and the expression of melanogenesis‐related molecules.…”
mentioning
confidence: 79%
“…This issue of the BJD includes an interesting piece of research by Kim and coworkers outlining a possible association between high‐mobility group box 1 (HMGB1) and vitiligo. HMGB1 is a DNA‐binding nonhistone protein that acts as a transcriptional regulator participating in DNA replication, recombination, transcription and repair.…”
mentioning
confidence: 99%